Differential associations between childhood trauma subtypes and adolescent HPA-axis functioning - Kuhlman, Kate R. (Psychoneuroendocrinology, 2015)
Studies examining the association between childhood trauma exposure and neuroendocrine functioning have returned inconsistent findings. To date, few studies have accounted for the role exposure to different types of childhood trauma may have on different neuroendocrine adaptations, and no study has examined this association using multiple indices of hypothalamic—pituitary—adrenal axis (HPA-axis) functioning. The purpose of this study was to characterize the unique associations between exposure to physical abuse, emotional abuse, and non-intentional trauma, and multiple indices of HPA-axis functioning. METHODS: A community sample of 138 youth (aged 9—16) completed the Socially Evaluated Cold Pressor Task (SE-CPT) while their parents completed the Early Trauma Inventory (ETI). All youth then collected 4 diurnal salivary cortisol samples at home across 2 consecutive weekdays. RESULTS: High reported exposure to non-intentional trauma was associated with intact diurnal regulation but elevated cortisol at bedtime, physical abuse was associated with faster reactivity to acute stress, and emotional abuse was associated with delayed recovery of cortisol following acute stress. Taken together, there was a heterogeneous relationship among different indices of HPA-axis functioning and trauma subtype. DISCUSSION: Different types of childhood trauma exposure are related to distinct anomalies in HPA-axis functioning. This study underscores the importance of research incorporating multiple indices of HPA-axis functioning to inform our understanding of the underlying neuroendocrine dysregulation that may later lead to stress-related psychopathology.